History of Ilmul Saidala (Unani Pharmacy) Through Ages: A Critical Appraisal and Current Scenario (Bangladesh Journal of Medical Science, 2022)
Ilmul Saidala (Unani pharmacy) is an important pharmaceutical branch of Unani System of Medicine, also known as Greco-Arabic medicine. Its historical evolution is intricately related with that of human’s disease and sufferings. The earlier records about the Ilmul Saidala reveal that the Greco-Roman civilization is credited with its origin and development. Then, the Arabs preserved their medical legacy, and enriched it with their pharmaceutical experiments, innovations, and newer formulations. Most of the physicians rendered voluminous compendium known as “Al-Qarābādhīn” (pharmacopoeia) on the pharmacy including pharmaceutical as well as cosmeceutical preparations. After the fifth century, the development in Unani Pharmacy has been greatly contributed by Arab physicians and the world acclaimed piece of knowledge from this period is Avicenna’s ‘Canon of Medicine’. The medical influences of the Arabs helped in further development, regulation, and advancement of pharmaceutical sciences in the European soil and evolved it as a distinctive institution of respect and public welfare. The vastness of knowledge of Greco-Arabic period can be judged from the fact that the contemporary innovations and developments in the pharmaceutical industry is primarily owed to the original contributions of Greek, Egyptian, and Arab philosophers and physicians, such as Hippocrates, Pedanios Dioscorides, Galen of Pergamon, Avicenna, Rhazes, Geber etc. In India, Mughals, especially emperor Akbar was very instrumental in the propagation of Unani medicine and had appointed Unani physicians in different cities of his territory. Later on, Khandan Shareefi (Shareefi family) and Khandan Azizi (Azizi family) played important roles in the promotion of Unani Pharmacy. In post-independence India , Hạkīm ‘Abd al-Hạmeed established Unani pharmacies on the lines of the modern pharmaceutical industry for the mass production of Unani formulations in compliance with Good Manufacturing Practice (GMP) guidelines. At present, Unani System of Medicine and its pharmacies enjoys the patronage of Government in India and other South-East Asian countries, such as Pakistan and Bangladesh along with post graduate education in Unani pharmacy. The present work is a sincere attempt of authors to critically appraise the Unani Pharmaceutical potentials from the past, the current waves of developments and issues, and their possible ways forward.Bangladesh Journal of Medical Science Vol. Vol. 21(1) 2022 Page : 24-36